ADVANTAGES AND DISADVANTAGES OF COMPACT YARN DEVICES ON SPINNING MACHINES - Yusupova , Ranoxon Kasimdjanovna (Educational Research in Universal Sciences, 2023)
As a result of the experiments, it was found that the yarn of the JV "Indorama Kokand Textile" is 36.2% less dense than the yarn of the JV "Pop FEN", 13.5% in relative hardness and several times higher in other indicators.